A High Capacity All Solid‐State Li‐Sulfur Battery Enabled by Conversion‐Intercalation Hybrid Cathode Architecture. (30th November 2020) - Xu, Shiqi; Kwok, Chun Yuen; Zhou, Laidong; Zhang, Zhizhen; Kochetkov, Ivan; Nazar, Linda F.
Abstract: As demands for electrochemical energy storage continue to rise, alternative electrochemistries to conventional Li‐ion batteries become more appealing. Here, an intercalation‐conversion hybrid cathode that combines intercalation‐type VS2 with conversion‐type sulfur chemistry to construct high performance solid‐state lithium‐sulfur batteries is reported. The layered VS2 nanomaterial features Li‐ion transport channels, metallic conductivity, and active capacity contribution, all of which provide an ideal platform for the solid state S/Li2 S redox couple to unlock its high gravimetric capacity. The S/VS2 /Li3 PS4 hybrid cathode composite is prepared by a facile, low‐cost, and low‐energy mechanical blending process. The S/VS2 /Li3 PS4 |Li3 PS4 |Li/In (or Li) all‐solid‐state cell exhibits sulfur utilization of ≈85%, with a Coulombic efficiency of close to 100%. High areal capacity up to 7.8 mA h cm −2 with an active material loading (S/VS2 ) as high as 15.5 mg cm −2 is achieved. Abstract : A S/VS2 /Li3 PS4 hybrid cathode exhibits sulfur utilization of ≈85% in an all‐solid state cell with a Li‐metal anode and coulombic efficiency of close to 100%. High areal capacity up to 7.8 mA h cm −2 is achieved with an active material loading (S/VS2 ) as high as 15.5 mg cm −2 .